Recurrent syncope, orthostatic hypotension and volatile hypertension: think outside the box - Thein Aung; Wuqiang Fan; Mahesh Krishnamurthy (Greater Baltimore Medical Center, 2013)
The baroreceptors in the neck and aortic arch are important regulators of sudden blood pressure changes. They are innervated by CN IX and X and synapse in the brainstem. Baroreceptor failure is an under-recognized cause of recurrent syncope, orthostatic hypotension, and volatile hypertension, which is refractory to and may in fact worsen with conventional treatments. Baroreflex failure can be the result of neck and chest radiation, head and neck surgery, and cerebrovascular accidents involving the brainstem nuclei. The management of baroreflex failure is a challenge since patient education, lifestyle changes, and family support are extremely important in managing blood pressure. Leg exercises and Thrombo-Embolic Deterrent Stockings (TED) stockings are important in treating orthostatic hypotension. Clonidine is the antihypertensive of choice for supine hypertension. Low-dose benzodiazepines are helpful in suppressing sympathetic surges. We have encountered two patients with baroreflex failure after chemotherapy and radiation to the neck or upper chest. Temporal relationship between symptoms onset and the history of head, neck, and upper chest radiation or trauma is important in reaching a diagnosis.